Answer:
When (-1,-4) is substituted into the second equation, the equation is true.
The ordered pair (-1,-4) is a solution to the system of linear equations.
When (-1,-4) is substituted into the first equation, the equation is true.
Step-by-step explanation:
Given
[tex]x - y = 3[/tex]
[tex]7x - y = -3[/tex]
Required
What is true about [tex](x,y) = (-1,-4)[/tex]
To do this, we substitute -1 for x and -4 for y in both equations;
For [tex]x - y = 3[/tex]
[tex]-1 - (-4) = 3[/tex]
[tex]-1 + 4 = 3[/tex]
[tex]3 = 3[/tex]
Hence: [tex](-1,-4)[/tex] is true for [tex]x - y = 3[/tex]
For [tex]7x - y = -3[/tex]
[tex]7(-1) - (-4) = -3[/tex]
[tex]-7 +4 = -3[/tex]
[tex]-3 = -3[/tex]
Hence: [tex](-1,-4)[/tex] is true for [tex]7x - y = -3[/tex]